Supporting State-approved Materials with the Values Clarification Task. (August 2019) - Manning, Shaun J.
Many teachers in Asian EFL situations report difficulties integrating communicative tasks into their classrooms. This study reports on an innovation in which opinion gap tasks were used to support the regular classwork of a middle school English class in Seoul, South Korea. The task had to reflect the learning objectives of the state-mandated textbook while encouraging students to speak up and express their opinions. The classroom teacher wanted to ensure students who had pre-studied the materials at after-school classes would still be engaged with the task. A values clarification (VC) task was developed for this purpose. This study reports how the VC task performance reflects the types of talk theorized to benefit language learning.